2013
DOI: 10.1021/jp4098342
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Gating of Charge Separation in Porphyrin Oligomer-Fullerene Systems

Abstract: The rate of the photoinduced charge-separation in C 60 -terminated butadiyne-linked porphyrin oligomers P n (n = 4, 6) is strongly influenced by their molecular conformation. In these systems, the presence of the butadiyne linkers gives rise to a broad distribution of conformations in the ground state, due to an almost barrierless rotation of individual porphyrin units in the oligomer chain. The conformational states of these oligomers, either twisted or planar, could be selected by varying the excitation wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…To do so, the majority of allosteric receptors and catalysts in the literature have made use of structural-based regulation, wherein activity is controlled via changes in the shape or steric confinement around active moieties . On the other hand, regulation of catalysts, allosteric or otherwise, based on electron-transfer and light-harvesting processes has generally been possible by using control mechanisms that instead tailor the electronic state of the active site. In natural systems, however, structural and electronic regulatory strategies often act synergistically to maximize the toggling between active states, with photosystem II (PSII) being a prime example (Figure A). Photoactive systems are indeed good targets for coupled regulatory strategies because the interactions between their active components are not only dependent on the electronic environment , but also highly sensitive to structural cues given the fundamental distance dependence of through-space phenomena such as electron and energy transfer. , The challenge has thus been to develop regulatory strategies to control inorganic catalysts by constructively harnessing the electronic and structural perturbations that occur upon analyte binding to an allosteric framework.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…To do so, the majority of allosteric receptors and catalysts in the literature have made use of structural-based regulation, wherein activity is controlled via changes in the shape or steric confinement around active moieties . On the other hand, regulation of catalysts, allosteric or otherwise, based on electron-transfer and light-harvesting processes has generally been possible by using control mechanisms that instead tailor the electronic state of the active site. In natural systems, however, structural and electronic regulatory strategies often act synergistically to maximize the toggling between active states, with photosystem II (PSII) being a prime example (Figure A). Photoactive systems are indeed good targets for coupled regulatory strategies because the interactions between their active components are not only dependent on the electronic environment , but also highly sensitive to structural cues given the fundamental distance dependence of through-space phenomena such as electron and energy transfer. , The challenge has thus been to develop regulatory strategies to control inorganic catalysts by constructively harnessing the electronic and structural perturbations that occur upon analyte binding to an allosteric framework.…”
Section: Introductionsupporting
confidence: 85%
“…10−13 Photoactive systems are indeed good targets for coupled regulatory strategies because the interactions between their active components are not only dependent on the electronic environment 14,15 but also highly sensitive to structural cues given the fundamental distance dependence of through-space phenomena such as electron and energy transfer. 16,17 The challenge has thus been to develop regulatory strategies to control inorganic catalysts by constructively harnessing the electronic and structural perturbations that occur upon analyte binding to an allosteric framework.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12). 43 For simplicity, these calculations were performed assuming coplanar porphyrins for the entire series P n (n = 1-4, 6, 8). Also earlier computational calculations of the electronic spectra of the dimer by Beljonne et al 44 demonstrated the enhanced stabilization of the excited states.…”
Section: Strongly Coupled Porphyrin Oligomersmentioning
confidence: 99%
“…These molecular wires are excellent candidates for charge- and energy-transport over distances of 5–20 nm. 2 4 , 9 However the synthesis of long monodisperse chains can be laborious. Here, we develop template-directed strategies for controlling the synthesis of linear porphyrin oligomers.…”
Section: Introductionmentioning
confidence: 99%